2018
DOI: 10.1017/jfm.2018.668
|View full text |Cite
|
Sign up to set email alerts
|

Very small insects use novel wing flapping and drag principle to generate the weight-supporting vertical force

Abstract: The effect of air viscosity on the flow around an insect wing increases as insect size decreases. For the smallest insects (wing length R below 1 mm), the viscous effect is so large that lift-generation mechanisms used by their larger counterparts become ineffective. How the weight-supporting vertical force is generated is unknown. To elucidate the aerodynamic mechanisms responsible, we measure the wing kinematics of the tiny wasp Encarsia formosa (0.6 mm R) in hovering or very slow ascending flight and comput… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 53 publications
2
64
0
Order By: Relevance
“…An idealized twodimensional computational study (Jones et al 2015) demonstrated such possibility of drag-based mean force generation by a cyclic motion of a flat plate. Three-dimensional numerical simulations of Encarsia formosa (Cheng and Sun 2018) and thrips Frankliniella occidentalis (Lyu et al 2019) with realistic wing kinematics also show cycle-average forces sufficient for body weight support, under the assumption that the wings are impermeable plates. However, until now, the force-generation capacity and aerodynamic function of the bristled wing morphology remains a largely open question.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 89%
See 3 more Smart Citations
“…An idealized twodimensional computational study (Jones et al 2015) demonstrated such possibility of drag-based mean force generation by a cyclic motion of a flat plate. Three-dimensional numerical simulations of Encarsia formosa (Cheng and Sun 2018) and thrips Frankliniella occidentalis (Lyu et al 2019) with realistic wing kinematics also show cycle-average forces sufficient for body weight support, under the assumption that the wings are impermeable plates. However, until now, the force-generation capacity and aerodynamic function of the bristled wing morphology remains a largely open question.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 89%
“…The drag-based flight mode in insects (Jones et al 2015) requires reciprocating motion of the wings: the drag should be larger when the wings move down than when they move up. It can be referred to as the "rowing mechanism" (Cheng and Sun 2018;Lyu et al 2019), for its similarity with swimming or paddling action that was already noticed in an early work by Horridge (1956).…”
Section: Paddling Effectiveness Factormentioning
confidence: 98%
See 2 more Smart Citations
“…Moving overset grids are employed owing to the relative motion of the wings and body. The flow solver is the same as that employed in several previous works of our group 14,19,20 and the description of the method is presented in the Supplementary Material, Supplementary S1. Tests of the computational grid are also given in the Supplementary Material, Supplementary S2.…”
Section: Reference Frames and Equations Of Motionmentioning
confidence: 99%